2012
DOI: 10.5539/gjhs.v4n4p139
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Relationship between Malaria Parasite Density and Some Haematological Parameters in Malaria Infected Male Subjects in Port Harcourt, Nigeria

Abstract: This study examined the experiential relationship between the parasite density and haematological parameters in male patients with Plasmodium falciparum infection in Port Harcourt, Nigeria reporting to malaria clinics. A total of one hundred and thirty-six (136) male patients were recruited. QBC haematological analysis, QBC malaria parasite specie identification and quantification and thin blood film for differential leucocytes count was used. The mean values of the haematological parameters in each quartile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In both the infested and basal (uninfested) groups, we found that lymphocytes are the most abundant leukocytes in the peripheral blood; however, eosinophils were scarce in the uninfested fishes but abundant in the infested ones, which correlates with other studies in fishes (ALVAREZ-PELLITERO, 2008;EZE EVELYN et al, 2012;PIERRARD et al, 2012;RUANE et al, 2000;SILVA-SOUZA et al, 2000). Neutrophils decrease steadily during the 4 weeks of infestation, which is consistent with a study by Tavares-Dias et al (2008).…”
Section: Discussionsupporting
confidence: 82%
“…In both the infested and basal (uninfested) groups, we found that lymphocytes are the most abundant leukocytes in the peripheral blood; however, eosinophils were scarce in the uninfested fishes but abundant in the infested ones, which correlates with other studies in fishes (ALVAREZ-PELLITERO, 2008;EZE EVELYN et al, 2012;PIERRARD et al, 2012;RUANE et al, 2000;SILVA-SOUZA et al, 2000). Neutrophils decrease steadily during the 4 weeks of infestation, which is consistent with a study by Tavares-Dias et al (2008).…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, microscopy is the gold standard in malaria diagnosis as it is able to detect low parasitaemia threshold of 100 parasites per microlitre of blood in the thin film and about 50 parasites per microlitre of blood in the thick film [ 5 ]; identify and describe species and stages, quantify parasite density and is also used for treatment response monitoring. The sensitivity and specificity of this diagnostic tool is however of great concern as skilled laboratory professionals trained in microscopy are needed to give reliable results [ 7 ]. Accurate diagnosis of malaria is important in reducing misdiagnosis of the disease and helps in identifying other fatal non-malarial causes of infection, reducing wastage of and possible resistance to antimalarial drugs and enables the effective management of febrile patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…An inverse correlation between the parasite densities with the lymphocyte count in P. falciparum infection and positive correlations of the parasite density with neutrophil and platelet counts in P. vivax and P. falciparum infection were reported by studies in Ghana and South Ethiopia [3], [7]. A mathematical model study also designated good relationships of the parasite density with neutrophil, lymphocyte, monocyte, and eosinophil count in P. falciparum infection [17]. Despite those discordances, insignificant correlations of parasite density, in both species, with hemoglobin concentration, leukocyte count, and monocyte count, in this study, agree with the previous studies [3], [7].…”
Section: Discussionmentioning
confidence: 62%